1848 Ala. Laws 121-22 - (:unkn) unknown (My University, 1848)
Prohibited any person or persons from receiving, keeping, or storing in any building within three miles of the Mobile River or Bay, gun-powder, gun-cotton, or other explosive material in larger quantities than one hundred pounds.
Keywords: GUNPOWDER - STORAGE